Ludwig Binswanger correspondence - Binswanger, Ludwig, 1881-1966.
TLsS (18 and 25 July 1957) from Binswanger to Vladimir Gurewich.
Psychiatrist and author.
Collection material in German.
Forms part of: Sigmund Freud collection.
Keywords: Gurewich, Vladimir -- Correspondence; Authors; Psychiatrists